PENGEMBANGAN MEDIA PEMBELAJARAN BOARD GAME WHO IS IT DALAM MATERI KEBERAGAMAN BUDAYA MATA PELAJARAN IPAS KELAS IV SD - Lala Salim; Jihan Afifah Magrisya Pelupessy; Taofik; Anggi Citra Apriliana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Based on the finding that students prefer game-based learning media, this research aims to develop a Who Is It Board Game to become a useful learning media for learning. In addition, the purpose of developing the learning media board game who is it is so that learning becomes more effective and students are not easily bored during the learning process. This research uses the Research and Development (R&D) method with the ADDIE model (analyze, design, development, implementation, evaluation). The research subjects were 31 fourth grade students of SDN Cawang 04 Pagi. Data collection instruments were validation sheets and questionnaires. The data analysis techniques used are validity analysis, practicality analysis and effectiveness analysis. The results of the Who Is It Board Game media validation by media experts and material experts, which by media experts obtained the results “very feasible” while by material experts obtained the results “feasible”. The results of the Field Test Evolution feasibility data analysis involving all students of class IV B SDN Cawang 04 showed a percentage of 84.20%, which indicates that the Who Is It Board Game media for learning Cultural Diversity in IPAS subjects is considered very practical and suitable for use in the learning process in the classroom.